Non-Invasive Blood Sugar Level Meter Based on Light Diffuse Reflection Ratio of 2-PPG Signals - Anchalee Manosueb; Kanyapat Moraruk; Kansadanan Saenyamas; Janjira Chintawan; Paramote Wardkein; Peeramed Chodkaveekityada (My University, 2025)
This article is studies of the noninvasive blood glucose measurement based on light diffuse reflection ratio of two PPG signal of red and infrared is proposed. Which the red light led and infrared light led is driven by 80 Hz and 190 Hz cosine wave frequency, respectively to generating two amplitude modulation that have photoplethysmography (PPG) as an information. It causes the two PPGs signal have immunity from ambient light and moving artifact noise and after that the amplitude modulation of two PPGs signal is taken to laptop computer by using soundcard interface and they are processed by two band pass filter center frequency 80 Hz and 190 Hz, respectively and next they are demodulated by squaring and passing through the low pass filter and take the output of LPF to be square rooting. the PPGs signal is appeared. Next, the two PPGs signal is to be calculated the reflection ratio by minimum and maximum of them, which the reflection ratio is to be evaluation Blood Glucose, in finally. The results from 10 volunteers show that this technique is possibility to measure BGP with noninvasive fashion. In the future work, the circuit should be improved, and more subject is experiment in order to more reliable.
Keywords: Spectroscopy Techniques in Biomedical and Chemical Research; Non-Invasive Vital Sign Monitoring; Spectroscopy and Chemometric Analyses